The Approaches To Teaching Foreign Languages - Absalamova Gulmira Sharifovna (Zien Journals, 2024)
In this article the structural approach focuses on sentence structure, with mastery of sentence structure being more important than vocabulary acquisition. Content words are also taught, guided by their usefulness, simplicity, and teachability. This approach is based on behaviorism theory and involves understanding the language's pattern and structure. Different languages have unique structures, such as Uzbek and English, which require thorough practice for naturalizing habits
Keywords: communicative language; structural approach; sentence pattern